Engendered Relations in the Global South - Canuday, Jose Jowel (Archīum Ateneo, 2018)
Excerpt: Gender as a framework of understanding social relations represents multiple fields of struggles that bring into question the discourse of sexual difference as a natural condition. One possible way of viewing gender is by looking at it as a discursive arena of contestation animating the social landscape of the global south. In this context, sexual relations are at once implicated by hierarchies of power underpinning precolonial structures of belonging, colonial hegemony, and postcolonial imaginations. Such hierarchies and realms of power become driving forces that produce and reproduce the socio-political agents that engender the assumptions of men and women as descriptive markers of physicality and sociality in space and time.